THE Effort To Increase Self Confidence Of The Competence Of Vocational High Students Through The Motivation: "Mindset Entrepreneurship In Supporting Independence Milenialpreneur In The Future" - Vembri Aulia Rahmi; Hadi Ismanto; Nanang Bagus Setiawan (Kontribusia : Research Dissemination for Community Development, 2020)
The Community service activities targeting students and teachers of Semen Gresik Vocational Schools are conducted to increase confidence in student competencies, including through the introduction, understanding, and strengthening motivation "Mindset Entrepreneurship" in the school environment. The purpose of the initial community service activity was aimed at responding to complaints about the problems of the school in academics (universities) that vocational student graduates were not working in the area of expertise possessed by students and also only a few students were able to create their jobs. The method used in community service uses an interpersonal approach to teachers and students using in-depth interviews with students and also teachers, interactive socialization, and discussion. The results of community service activities with Semen Gresik vocational partners provided positive results, both according to the perception of teachers and students, namely: (1) an increase in understanding of the problems along with finding solutions for teachers on the causes of low entrepreneurial interest for vocational students; (2) mental growth of students' confidence from their competence, after experiencing a strengthening of motivation on the principle of entrepreneurship (3) increasing insight and knowledge for students and teachers on the important role of entrepreneurship in the current digitalization era.